Human Rights during the COVID-19 Pandemic in Hungary with Special Regard to the Right to Have Contact - Szeibert, Orsolya (Medicine, Law & Society, 2021)
In Hungary, the government declared a state of danger in March 2020 as a consequence of the COVID-19 pandemic. The state of danger was lifted in June, but epidemological preparedness and state of medical crisis were declared by a government decree. In November 2020, the state of danger was declared for the second time, while epidemological preparedness was maintained. In February 2021, the state of danger was declared again. The list of the legal rules which changed and have been continuously changing because of the COVID-19 pandemic since March 2020 is extremly long and the new provision or the modifications have been heavily influencing the population's everyday life. The aim of this paper is to overview primarily the restrictions affecting human rights with special regard to the right to have contact as one of the patients' rights. Important issues of the parent-child contact affected by the COVID-19 pandemic is discussed, as well.